Effects of different sintering temperatures on thermal, physical, and morphological of SiO2-Na2O-CaO-P2O5 based glass-ceramic system from vitreous and ceramic wastes - Baharuddin Pallan, Nur Fadilah; Matori, Khamirul Amin; Hashim, Mansor; Azis, Raba'ah Syahidah; Zainuddin, Norhazlin; Baharuddin Pallan, Nor Faizah; Mohd Idris, Fadzidah; Ibrahim, Idza Riati; Loy, Chee Wah; Rusly, Siti Nor Ain; Adnin, Noorfauzana; Ahmad Khiri, Mohammad Zulhasif; et al. (International Institute for the Science of Sintering, 2019)
This research involved comprehensive studies on thermal, physical, and morphological properties of SiO2-Na2O-CaO-P2O5 (SNCP) glass-ceramic at various sintering temperatures. The study in SNCP glass-ceramic using soda-lime-silica (SLS) wastes glass and clam shell (CS) wastes as the main raw of materials via conventional melt-quenching technique and solid state sintering are interesting and challenging by considering the research using waste materials to fabricate novel SNCP glass-ceramic. The main peaks, Na3PO4 and Ca3Na6Si6O18 were assigned to high crystallization temperature (Tc) at 650-950 °C. The density of samples increases at 550-750 °C and decreases at 850-950 °C due to the increase of sample thickness and higher specific volume at high sintering temperature. FESEM micrograph showed that existed porous increased at sintering temperature 850-950 °C contributes effect to low densification of the sample.